Religious and cultural food: at the crossroads of science and ethics - Ahmad Fadzillah, Nurrulhidayah; Mohd Sukri, Siti Jamilah; Othman, Rashidi; Jamaludin, Mohammad Aizat; Rosman, Arieff Salleh; Rohman, Abdul (Woodhead Publishing, 2018)
The existence of different religions around the world is not intended to create hostility, but to establish harmony and peace both here and hereafter. The food and drinks that we eat create our blood, give us energy, repair broken parts of our cells and tissues, and influence our thinking and activities. This chapter has compared and examined how five main religions, Christianity, Islam, Buddhism, Hinduism, and Jews, have influenced people's ethics on the selection of menu and their scientific points of view. Last but not the least, scientific explanations are given to show how the religious food and drinks are not just dogmatic, but have rationale to be practiced even in the modern time in maintaining both physical and spiritual health. The main purpose is not to insult any religious practices, but to help the readers rethink what type of food ethics provides the best solution for their physical and mental well-being.